Anti-inflammatory Effect of Ghrelin in Lymphoblastoid Cell Lines From Children With Autism Spectrum Disorder - Yamashita, Yasunori; Makinodan, Manabu; Toritsuka, Michihiro; Yamauchi, Takahira; Ikawa, Daisuke; Kimoto, Sohei; Komori, Takashi; Takada, Ryohei; Kayashima, Yoshinori; Hamano-Iwasa, Kaori; Tsujii, Masatsugu; Matsuzaki, Hideo; et al. (Frontiers in Psychiatry, 2019)
The gut hormone ghrelin has been implicated in a variety of functional roles in the central nervous system through the brain-gut axis, one of which is an anti-inflammatory effect. An aberrant brain-gut axis producing immune dysfunction has been implicated in the pathobiology of autism spectrum disorder (ASD), and elevated expression of inflammatory markers has been shown in blood and brain tissue from subjects with ASD. We hypothesized that ghrelin may mitigate this effect,. Lymphoblastoid cell lines from typically developed children (TD-C) (N = 20) and children with ASD (ASD-C) (N = 20) were cultured with PBS or human ghrelin (0.01 μM) for 24 hours, and mRNA expression levels of the inflammation-related molecules interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and nuclear factor kappa B (NF-κB) were measured to examine the effects of ghrelin as an anti-inflammatory agent. Expression levels of TNF-α and NF-κB mRNA, but not IL-1β or IL-6, were significantly elevated in ASD-C compared to TD-C. Ghrelin showed a tendency to reduce the expression of TNF-α and NF-κB, but this was not statistically significant. Considering the heterogenous pathobiology of ASD, we examined the effects of ghrelin on TD-C and ASD-C with expression levels of TNF-α and NF-κB in the highest and lowest quartiles. We found that ghrelin markedly reduced mRNA expression of TNF-α and NF-κB s in ASD-C with highest-quartile expression, but there were no effects in ASD-C with lowest-quartile expression, TD-C with highest quartile expression, or TD-C with lowest quartile expression. Together, these findings suggest that ghrelin has potential as a novel therapeutic agent for ASD with inflammation and/or immune dysfunction.